2015
DOI: 10.1159/000375503
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Methylation with Green Tea Catechins

Abstract: Aberrant epigenetic alterations in the genome such as DNA methylation play a significant role in cancer development. Green tea catechins have been reported to modulate epigenetic processes. This review aims to synthesize evidence on the modulation of DNA methylation by green tea catechins. Green tea catechins have been reported to reverse DNA methylation of tumor suppressor genes and increase transcription of these genes. Green tea catechins and especially epigallocatechin gallate modulate DNA methylation by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…It has been reported that flavonoids modulate DNA methylation by attenuating the effect of DNMTs, thus inducing a reduction in overall DNA methylation [34,42]. The exact mechanism of DNMT1 inhibition by flavonoids is still under study but it may take place by, for example, direct enzyme inhibition, indirect enzyme inhibition, reduced DNMT1 expression and translation, or interaction with methyl-CpG binding domain proteins [42]. Specifically, we checked whether GSPE was affecting the gene expression of DNMT1, which is the methyltransferase responsible for maintaining DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that flavonoids modulate DNA methylation by attenuating the effect of DNMTs, thus inducing a reduction in overall DNA methylation [34,42]. The exact mechanism of DNMT1 inhibition by flavonoids is still under study but it may take place by, for example, direct enzyme inhibition, indirect enzyme inhibition, reduced DNMT1 expression and translation, or interaction with methyl-CpG binding domain proteins [42]. Specifically, we checked whether GSPE was affecting the gene expression of DNMT1, which is the methyltransferase responsible for maintaining DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Some catechins inhibited mammalian DNA‐polymerase, DNA‐methyltransferase (DNMT) and ribonuclease A (RNase A) (Table ), with EGCG being the strongest inhibitor with IC 50 values ranging between 10 −7 M (DNMT9) and 10 −5 M (RNase A). Among these enzymes, DNMT is involved in the hypermethylation of the promoter regions, which is an important mechanism for silencing the expression of many significant genes in cancer (Yiannakopoulou, ). However, data from meta‐analyses provided contrasting results and indicated that the associations differ according to sex, ethnicity, cancer and tea types (Zeng et al , ; Ma et al , ; Zhu et al , ; Huang et al , ; Zhou et al , ).…”
Section: Enzymatic Inhibitionmentioning
confidence: 99%
“…Green tea, a notable antioxidant product, has an extensive in vitro studies of its properties, including systemic antioxidant, anti-inflammatory activities, prevention of DNA damage [30], immunoregulation, and antiphotoaging properties. However, only one randomized, double-blind, placebo-controlled trial indicates an increase in photosensitivity threshold and improves skin physiology following a daily intake.…”
Section: Camellia Sinensismentioning
confidence: 99%